(untitled) (European Journal of Multidisciplinary Studies, 2017)
Organizational efficiency is generally defined as a measure of relation between the input resources and output generated within a system. Organizational efficiency in public and private sector enterprises and communities plays a key role in ensuring value creation, and thereby, ensuring economic and social sustainability of societies with effective and minimal use of resources, reduced waste and small ecological footprint. Transforming an organization is all about changing a laggard organization to an agile and responsive entity, which foresees changes, willing and adaptive to changes proactively rather, being reactive to changes, which are forced by the operating environments. A proactive organization with visionary leadership foreseeing the challenges establishes mitigation plans to overcome or reduce the impact triggered by operational challenges, while a reactive organization will be impacted by the operational challenges before it initiates changes based on the impact assessment. Transformation of an organization reduces operational costs by eliminating duplications and non-value adding processes (Robbins, 2012). The paradigm of sustainable transformation of organizations has three main components which are interactively functioning: leadership and management, human resources, and organizational culture. Sustainability is defined as ‘responsibility of an organization in sustained generation of economic, environmental and social benefits’ (Gardelliano, 2005). Organization management often gets caught in the contradiction between sustainability and profitability. The shareholders / stakeholders would want short term profitability of an organization while societies around the world are increasingly demanding corporations to be environmentally and socially responsible in its operations with utmost importance being given to their human and natural resources and communities that they operate in. Sustainability also depends on Innovation and Knowledge Development. In a knowledge economy, key engine of growth is knowledge. An economy in which knowledge is acquired, created, disseminated and applied to enhance economic development is known a knowledge economy (Building Knowledge Economy, WBI, 2011). An effective ecosystem which nurtures innovation is based on outputs generated from knowledge centers like universities, research centers, schools, consultancy agencies and other organizations engaged in similar endeavors. The knowledge generated in such centers is applied though right tools to enhance the wellbeing of humans and sustainability of organizations. This paper focuses on the impact of human resource function on the organizational transformation for efficiency improvement.